Community Enterprise Strengthening: Case study of Indigenous Food Entrepreneurs in Rayong Province - suvarnakuta, khompol (Journal of Social Development and Management Strategy, 2024)
This research aims to study the strength of local food enterprise community businesses in Ban Thale Noi, Rayong Province, using qualitative research techniques. In-depth interviews were conducted with 12 key informants. The findings revealed that the strength of these local food enterprise communities requires further development. The Ban Thale Noi community has promoted the use of Pak Krachab, a local vegetable, as a core ingredient in traditional local dishes, integrating it into the community’s lifestyle to enhance community-based tourism. The community has also adapted and utilized local resources to improve production processes in alignment with market conditions, fostering self-reliance. However, several challenges remain for these community enterprises, including: (1) reliance on external markets, and (2) issues in internal management and income distribution within the community enterprise group. Key recommendations include: (1) To reduce reliance on external markets, the market base should be expanded to link with existing community-based tourism. This can be achieved by introducing additional tourism activities, such as a signature dish experience “Plant, Harvest, Cook, and Taste Local Vegetables and Traditional Cuisine” or the activity “Junior Tour Guides Take the Elderly on a Tour of the Pak Krachab Community.” Increasing the number of tourists can also be supported by encouraging school children, who commute to nearby urban areas for education, to create activities that attract elderly urban communities to visit the Pak Krachab community, and (2) In terms of management and income distribution within the Pak Krachab community enterprise group, it is recommended to ensure continuous, consistent, and fair allocation of responsibilities among members involved in tourism activities, fostering active participation and equitable sharing